ECONOMIC SUSTAINABILITY OF AN ALTERNATIVE FORM OF INCENTIVIZING PHARMACEUTICAL INNOVATION: THOMAS POGGE’S PROPOSAL - CASSONE, Alberto; AMISANO, Franco (Annales Universitatis Apulensis Series Oeconomica; Vol 1 No 16 (2014): Annales Universitatis Apulensis Series Oeconomica, 2014)
The research and development of new drugs and vaccines is costly. Current economic incentives for pharmaceutical research come from intellectual property policies that grant innovators the exclusive monopoly for marketing their discoveries. The existing patent system does not encourage the development of drugs whose sale would not generate high returns. As a result, little is invested in researching and developing medicines that could cure or prevent rampant disease and death among the poorest segments of the global population, particularly in developing countries. Philosopher Thomas Pogge has recently addressed this problem from an ethical point of view, proposing an alternative reward scheme based on the therapeutic effectiveness of new products. This paper provides an analytical review of Pogge’s reform proposal from an economics perspective. The main question is whether the alternative incentive system is effective enough to promote the discovery of new medicines for neglected diseases. Theoretical models are defined to assess the required reward of pharmaceutical innovation within the framework of Pogge’s proposal. The mathematical approach taken is mainly based on the investment under uncertainty concept. Results from the simulations performed indicate that Pogge’s scheme may be effective mainly for widespread diseases like malaria and HIV.